Solve 0 = -w - 4*j + 1, -5*w - 3*j = -6*j + 18 for w.
-3
Solve -5*c + 5*w - 6*w - 7 = 0, -3*w - 8 = 2*c for c.
-1
Solve -4*i - y = y + 10, 2*i - 4*y = 0 for i.
-2
Solve m = 5*o - 3, 3*m + 5*o + 3 = 14 for m.
2
Solve -4*y - 4*c = -16, 0*y + 5*c = 3*y + 20 for y.
0
Solve -j - d = 7, -4*j - 23 = d + 2 for j.
-6
Solve -6 = 3*a - 3*n, -4*a - n - 3 + 5 = 0 for a.
0
Solve 3*g = -4*x + 23, 2*g - 3*g + 5*x - 5 = 0 for g.
5
Solve -3*n + 5 = 2*m, -10*n + 3 = -6*n - m for n.
1
Solve -27 = 5*h - 4*k + 9, 5*k - 40 = 5*h for h.
-4